How can the EQA provider encourage the participation in Pre-Analytical schemes - Cardoso, Ana (2018)
Providing a quality sample and ensuring the best laboratory practices should be the aim of Pre-Analytical Phase. With analytical phase strictly controlled, pre-analytical phase should be the laboratories target for improvement processes. Concerning to this, it is important to have in place a proper system for error detection for this extra-analytical phase and to be able to detect errors that have a significant negative effect on sample quality and patient health. Although laboratory managers are becoming to concern about these issues, the participation rate on the national program on pre-analytical phase is still very low, which means that the EQA provider should have an intervention more active than it has with the analytical phase. In order to contradict this weak participation and to reach the laboratories needs, PNAEQ (Programa Nacional de Avaliação Externa da Qualidade) has launched two types of schemes in which laboratories participation depends mainly of the EQA provider. One is the “mystery client”, which simulates a real life scenario to verify if the information provided to the patient depends on the laboratory collaborator. The other one is a presential audit, which identify some of the real errors occurred during the blood drawing. The aim of these two types of surveys is to demonstrate that most of the pre-analytical errors are detectable and, more important than that, they can be corrected or eliminated when pre-analytical phase is controlled.